MEASURING PEDESTRIANS’ SATISFACTION OF URBAN ENVIRONMENT UNDER TRANSIT ORIENTED DEVELOPMENT (TOD): A CASE STUDY OF BANGKOK METROPOLITAN, THAILAND - Pawinee Iamtrakul; Junyi Zhang (Lowland Technology International, 2014)
The problem of continuous increasing of carbon dioxide emissions in line with higher energy demand in Thailand has been called for attention under global warming conditions. In order to tackle with this problem, transportation was found as a major sector in an escalation of energy consumption which is the cause of carbon emission. As a developing country, infrastructure development has always been focused on an increasing of supply side, while less promote on public transportation and almost ignore for nonmotorization. The purpose of this study is to propose the method for measuring factors associated with pattern of walking behavior in connecting to public transportation usage by selecting Bangkok Mass Transit System as a case study. The results demonstrated different dimension of built environment aspects influence on different level of pedestrians’ satisfaction. Thus, transportation planners should consider different context of urban area as a key parameter to provide future metropolitan transportation while allocate appropriate strategy and management policy to create walkable urban place to shift in travel mode from vehicles to transit or active transportation.